Improving Building Information Modelling (Bim) In Technical Vocational Education And Training (Tvet) In Malaysia Polytechnics. - Ismail, Nurul Hazalia (2024)
This study investigates the Building Information Modelling (BIM) in Technical Vocational Education and Training (TVET) in Malaysia Polytechnics, particularly for the Diploma in Architecture, Engineering, and Construction (AEC) courses. The objectives are to critically assess the improvement of BIM in the TVET curriculum, evaluate educators’ awareness of BIM, identify the barriers encountered, and propose strategies to enhance BIM education in these institutions. Despite BIM's critical role in the AEC industry, its implementation within the Malaysian TVET curriculum faces significant obstacles, including the absence of a standardised approach, limited resources, and gaps in both practical and theoretical BIM expertise among educators. While the subject has garnered attention, research specifically addressing BIM education within the context of Malaysian higher education remains insufficient. A quantitative methodology was used, utilising a comprehensive questionnaire designed to gather data on educators' demographics, levels of BIM awareness, and the barriers to BIM implementation. The findings reveal that 50% of educators possess only moderate BIM skills, with a considerable number lacking adequate qualifications in the field. The study underscores the necessity for continuous curriculum development, improvement of the existing BIM education framework, and the removal of barriers impeding effective BIM education. The proposed strategies include enhancing educators’ BIM knowledge, ensuring access to up-to-date software, and integrating practical workshops into the curriculum.